Parvovirus B19 Achievements and Challenges. (29th April 2013) - Gallinella, Giorgio
Abstract : Parvovirus B19 is a widespread human pathogenic virus, member of the Erythrovirus genus in the Parvoviridae family. Infection can be associated with an ample range of pathologies and clinical manifestations, whose characteristics and outcomes depend on the interplay between the pathogenetic potential of the virus, its adaptation to different cellular environments, and the physiological and immune status of the infected individuals. The scope of this review is the advances in knowledge on the biological characteristics of the virus and of virus-host relationships; in particular, the interactions of the virus with different cellular environments in terms of tropism and ability to achieve a productive replicative cycle, or, on the contrary, to establish persistence; the consequences of infection in terms of interference with the cell physiology; the process of recognition of the virus by the innate or adaptive immune system, hence the role of the immune system in controlling the infection or in the development of clinical manifestations. Linked to these issues is the continuous effort to develop better diagnostic algorithms and methods and the need for development of prophylactic and therapeutic options for B19V infections.